The effect of intensive training on developing specific speed endurance and performance in the 100m freestyle swimming event for young people - Sultan, Asst.L. Rana Qais; Jassim, Asst.L. Shahd Marzouq (Sulaimani Journal for Humanities, 2026)
This research aims to develop intensive training exercises to improve speed endurance and performance in the 100m freestyle for young swimmers, and to identify effective intensive training methods for developing speed endurance and performance in the 100m freestyle for young swimmers. To achieve the objective, the researcher used a pre-test/post-test experimental method, deemed suitable for the research problem. The research sample was selected purposively, consisting of ten (10) swimmers from the Iraqi national youth swimming team, aged 15-17 years, during the 2023-2024 sports season. These swimmers train daily at the training center of the Iraqi Central Swimming Federation, the Al-Shaab Olympic Indoor Swimming Pool in Baghdad, and have achieved numerous accomplishments through their participation in local and international championships. The researcher administered pre-tests and post-tests to the research sample and performed appropriate statistical analyses. The researcher concluded that the intensive training method was effective in developing the speed endurance and performance of the 100-meter freestyle swimmers in the research sample, and that the exercises used contributed to improving the speed endurance and performance of the 100-meter freestyle swimmers. The researcher concluded that the exercises used contributed to developing the speed endurance and performance of the 100-meter freestyle swimmers. The researcher recommends adopting the intensive training method she developed for training young swimmers to improve their speed endurance and performance in swimming. She also emphasizes the importance of developing specific speed endurance, given its direct impact on performance in short-distance swimming events. Keywords: Intensive training method, specific speed endurance.